Turkish public diplomacy: current understanding, actors, and applications - KÖKSOY, ERGÜN; KAVOĞLU, SAMET (IGI Global, 2023)
This study aims to analyze the current understanding, actors, and applications in Turkish public diplomacy of today. As an essential part of Turkish foreign policy to become both a formidable power in its region and a global actor, Turkish public diplomacy has seen a rapid rise in terms of its development since the early 2000s, becoming more institutionalized while increasing the number of applications. This chapter reviews and evaluates the current features of the afore-mentioned development and its outlook through scientific papers and arguments on Turkish public diplomacy, and the activities of Turkish institutions dealing with the selfsame subject. To this end, it utilizes qualitative research methods of literature review, document and descriptive analysis, with the hopes of contributing to the current international literature on the current outlook of Turkish public diplomacy.
Keywords: Sosyal ve Beşeri Bilimler; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Mass Communications and Mass Media; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; İLETİŞİM; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; COMMUNICATION; İletişim; Sosyal Bilimler ve Beşeri Bilimler; Communication; Social Sciences & Humanities